Recent advances in process engineering and upcoming applications of metal–organic frameworks - Ryu, UnJin (Coord Chem Rev, 2021)
Progress in metal–organic frameworks (MOFs) has advanced from fundamental chemistry to engineering processes and applications, resulting in new industrial opportunities. The unique features of MOFs, such as their permanent porosity, high surface area, and structural flexibility, continue to draw industrial interest outside the traditional MOF field, both to solve existing challenges and to create new businesses. In this context, diverse research has been directed toward commercializing MOFs, but such studies have been performed according to a variety of individual goals. Therefore, there have been limited opportunities to share the challenges, goals, and findings with most of the MOF field. In this review, we examine the issues and demands for MOF commercialization and investigate recent advances in MOF process engineering and applications. Specifically, we discuss the criteria for MOF commercialization from the views of stability, producibility, regulations, and production cost. This review covers progress in the mass production and formation of MOFs along with future applications that are not currently well known but have high potential for new areas of MOF commercialization.